أثر استخدام استراتيجية الصف المقلوب في تحصيل طلاب الصف الثالث المتوسط في مقرر الحاسب الآلي - آل مسعد، أحمد بن زيد بن عبدالعزيز; الدوسري، سعيد مبارك (جامعة الأمير سطام بن عبدالعزيز, 2018)
This study aimed to investigate the impact of the flipped classroom on the academic achievement of the third intermediate students in the cognitive skills (remembering, comprehension, application) in Bara’ Bin Malik intermediate school in Riyadh within the computer course. The researcher used the quasi-experimental research to achieve the aim of this research. The research sample consisted of 42 students divided into two groups , one is the control group of 21 students that have been taught in the traditional way , and the other is the experimental group of 21 students that have been taught by the flipped classroom method through the presentation of the content to students at their places through YouTube, Snapchat application and Twitter, and allow class time for discussion and conduct educational activities about the lesson. Using achievement test, the results indicated that there is an impact on the level of student achievement at cognitive levels (remembering, understanding, application) for the experimental group, The present study recommends encourage teachers using the flipped classroom on the school courses, and the necessity to hold training courses and workshops for teachers and students to introduce them to the concept of the flipped classroom and methods of implementation.
هدفت الدارسة إلى معرفة أثر استخدم استراتيجية الصف المقلوب في تحصيل طلاب الصف الثالث المتوسط للمهارات المعرفية (التذكر، الفهم، التطبيق) بمدرسة البراء بن مالك المتوسطة في مدينة الرياض في إطار مقرر الحاسب الآلي، وقد استخدم المنهج شبه التجريبي لتحقيق الهدف، وقد تكونت عينة الدراسة من ٤٢ طالبا موزعين على مجموعتين: إحداهما ضابطة، شملت ٢١ طالبا، درسوا بالطريقة التقليدية، والأخرى تجريبية، شملت ٢١ طالبا درسوا بطريقة الصف المقلوب، من خلال عرض محتوى الدروس للطلاب في منازلهم عبر موقع اليوتيوب Youtube وتطبيق سناب شات Snapchat وموقع تويتر Twitter. وتخصيص وقت الحصة المدرسية لإجراء المناقشات والنشاطات التعليمية المختلفة حول الدرس، وباستخدام الاختبار التحصيلي، أظهرت النتائج وجود أثر في مستوى تحصيل طلاب المجموعة التجريبية، عند المستويات المعرفية (التذكر، الفهم، التطبيق) وتوصلت الدراسة إلى توصيات ومقترحات منها: تشجيع المعلمين على استخدام طريقة الصف المقلوب في تدريسهم للمقررات التعليمية، والحاجة إلى إجراء دورات تدريبية، وورش عمل، للمعلمين والطلاب؛ لتعريفهم بمفهوم الصف المقلوب، وطرق تنفيذه.
Keywords: المرحلة المتوسطة -- تدريس الحاسب الآلي -- استراتيجية الصف المقلوب -- التعلم المدمج -- التحصيل الدراسي -- المهارات المعرفية -- شبكات التواصل الاجتماعي -- مدينة الرياض -- السعودية